Productivity and quality of Moina sp. cultivated with various culture medium - Shidik, Taufik Shidik Adi Nugroho; Ekasari, Julie; Jusadi, Dedi; Setiawati, Mia (Jurnal Akuakultur Indonesia, 2021)
Cultivation of Moina sp is still constrained by its quality, productivity, and sustainability. The alternative solution is the use of cultivation media materials that have high nutritional content and easily available in large quantities to support the quality and productivity of Moina sp. and meet the needs of live feed. The objective of the study was to evaluate the effect of various culture medium on the productivity and nutritional quality of Moina sp.. Five culture media were tested in laboratory scale, i.e. organic ingredient (BO), Chlorella sp. (Ch), Chlorella sp. + organic ingredients (ChBO), biofloc (BF) and biofloc + organic ingredients (BFBO). While in mass scale, four culture media were tested, i.e. Chlorella sp. (Ch), Chlorella sp. + Organic Ingredients (ChBO), Biofloc (BF) and Biofloc + Organic Ingredients (BFBO). The peaks of Moina sp. density in different treatments were achieved in different days. ChBO treatments significantly had higher productivity (P<0.05). The highest protein content was found in Moina sp. cultured with ChBO media, even higher than artemia. Moina sp. cultured with Chlorella sp. (Ch) showed the highest PUFA (Poly Unsaturated Fatty Acids) contents, while the highest MUFA (mono unsaturated fatty acids) contents was obtained from Moina sp. cultured with BFBO media lower than artemia. The study results indicates that different culture media produces different productivity and nutrient quality of Moina sp. The organic material combination of Chlorella sp. + organic material (ChBO) was the best media to improve the productivity and protein quality of Moina sp. Keywords : Biofloc, Chlorella sp., Moina sp., organic matter, productivity, quality ABSTRAK Budidaya Moina sp. masih terkendala pada kualitas, produktivitas dan kestabilan dalam ketersediaannya. Untuk itu diperlukan penggunaan bahan media budidaya yang memiliki kandungan nutrisi tinggi dan mudah didapat dalam jumlah banyak untuk mendukung kualitas dan produktivitas Moina sp. demi memenuhi kebutuhan pakan hidup. Tujuan penelitian yaitu mengevaluasi pengaruh berbagai media budidaya terhadap produktivitas dan kualitas nutrisi Moina sp. Lima media kultur yang diuji dalam penelitian laboratorium yaitu Bahan Organik (BO), Chlorella sp. (Ch), Chlorella sp. + Bahan Organik (ChBO), Bioflok (BF) dan Bioflok + Bahan Organik (BFBO). Sedangkan pada penelitian skala massal diuji empat media kultur yaitu Chlorella sp. (Ch), Chlorella sp. + Bahan Organik (ChBO), Bioflok (BF) dan Bioflok + Bahan Organik (BFBO). Puncak kepadatan Moina sp. pada tiap perlakuan dicapai pada hari yang berbeda. Perlakuan ChBO memiliki produktivitas yang lebih tinggi (P<0,05). Kandungan protein Moina sp. tertinggi ditemukan pada media ChBO dan bahkan lebih tinggi dari pada artemia. Moina sp. yang dibudidayakan dengan Chlorella sp. (Ch), menunjukkan kandungan PUFA tertinggi, sedangkan kandungan MUFA yang tertinggi terdapat pada Moina sp. yang dibudidayakan dengan bahan media BFBO namun masih lebih rendah jika dibandingkan dengan kandungan pada artemia. Hasil penelitian menunjukkan media kultur yang berbeda menghasilkan produktivitas dan kualitas nutrisi moina yang berbeda. Kombinasi bahan organik Chlorella + bahan organik (ChBO) merupakan media terbaik dibandingkan dengan perlakuan lainnya untuk meningkatkan produktivitas dan kualitas nutrisi terutama protein Moina sp. Kata kunci : Bioflok, Chlorella sp., Moina sp., bahan organik, produktivitas, kualitas